Healthy Living Movement Assistance to Maintain Dental and Oral Health in Children: A Community Service at SD Negeri 15 Fafanlap, South Misool District, Raja Ampat Regency, Southwest Papua, Indonesia - Fatimah, Fatimah; Nompo, Rifki Sakinah; Fitriani, Fitriani; Wamea, Yoneta (Indonesian Community Empowerment Journal, 2024)
Optimal dental and oral health is an important aspect in children's growth and development. However, in remote areas such as South Misool, Raja Ampat, access to dental health information and services is still limited. This encourages the need for community service to increase awareness and practice of maintaining dental and oral health in children. This community service was carried out at SD Negeri 15 Fafanlap involving 120 students in grades 1-6. The methods used include: (1) interactive education about dental and oral health, (2) demonstration and training on correct tooth brushing practices, (3) distribution of free brushes and toothpaste, (4) simple dental examinations, and (5) monitoring periodically for 6 months. After the intervention, there was a significant increase in students' knowledge about dental and oral health. The ability to brush teeth properly also increases rapidly, as indicated by a reduction in dental plaque. In addition, positive behavioral changes occurred with increased frequency of tooth brushing and use of fluoride toothpaste. This community service succeeded in increasing awareness, knowledge and practice of maintaining oral health among children at SD Negeri 15 Fafanlap. It is hoped that the continuation of the program and replication in other areas will have a wider impact on the dental and oral health of Indonesian children.